y+16=23

Simple and best practice solution for y+16=23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y+16=23 equation:


Simplifying
y + 16 = 23

Reorder the terms:
16 + y = 23

Solving
16 + y = 23

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-16' to each side of the equation.
16 + -16 + y = 23 + -16

Combine like terms: 16 + -16 = 0
0 + y = 23 + -16
y = 23 + -16

Combine like terms: 23 + -16 = 7
y = 7

Simplifying
y = 7

See similar equations:

| 33,000+1.4=121,200 | | 4x+(4-x)= | | 7x-28=7x+21 | | 5+7x=11x+7x | | -6(11-8x)=12 | | -4.9x^2+30.5x=0 | | 4x+8x-2x=10x | | 5(134x+153)=4,785 | | 9n=-6+10n | | -3(2x+2)=-24 | | -13=24+5(x-3.4) | | -8y+10=-7y | | 2z^2+2z+1=0 | | 56x-8=12-3x | | 148=64+6x | | 2y+5-y=-3(y-6) | | (2+4)+4(383949+73838)= | | 6x-9-4x+2= | | w*4.7+(1-w)*11.8=10 | | 3(175x+152)=2,556 | | 10-5(x-6)=115 | | -2sin^2(x)+3cos(x)+3=0 | | (3+b)*(3-b-a-2)+(a-1)*(b-1)= | | 4(4x-3)=12 | | 18(4-3x)=162 | | 30+00.20=94 | | 464+7p=700 | | 30+20=94 | | 5w+11=-19+11w | | 3(2x+4y)=12 | | 6+f=11 | | -25+y=65 |

Equations solver categories